Risk factors and outcome of patients with symptomatic intracranial stenosis presenting with lacunar stroke - Khan, Amir (2012)
BACKGROUND AND PURPOSE: We hypothesized that patients with intracranial stenosis with lacunar stroke presentations would face lower risks of recurrent stroke than those with index non-lacunar strokes, and that their recurrent strokes would predominantly be lacunar. METHODS: We analyzed subjects enrolled with an index stroke into the Warfarin Aspirin Symptomatic Intracranial Disease (WASID) trial. The index stroke was classified as lacunar or non-lacunar. The primary endpoint was recurrent ischemic stroke. Cox proportional hazard models were generated with stratification for severity of stenosis. RESULTS: 347 subjects were enrolled after an index stroke, 38 were lacunar and 309 were non-lacunar. Over a mean follow-up of 1.8 years there was no significant difference in stroke recurrence between patients whose index stroke was lacunar (7/38; 18%) vs. non-lacunar (69/309; 22%) (HR 0.79, 95%CI:0.36–1.71). Further, no significant differences were found when groups were stratified by 50–69% stenosis (HR 0.50, 95%CI:0.12–2.1) and ≥70% stenosis (HR 0.87, 95%CI:0.34–2.2). Of the 7 recurrent strokes in patients whose index stroke was lacunar, all 7 were non-lacunar and 3 were in the territory of the stenotic artery. CONCLUSIONS: In patients with symptomatic intracranial stenosis, the risk of recurrent stroke was similar in patients who presented with lacunar and non-lacunar strokes, and recurrent strokes in patients presenting with lacunar stroke were typically non-lacunar. These findings suggest that the pathophysiology of these strokes is related to the stenosis rather than small vessel disease. Patients presenting with lacunar strokes should be included in trials investigating secondary prevention for symptomatic intracranial stenosis.